2020
DOI: 10.3171/2020.3.spine2016
|View full text |Cite
|
Sign up to set email alerts
|

Single- versus dual-attending strategy for spinal deformity surgery: 2-year experience and systematic review of the literature

Abstract: OBJECTIVEAdult spinal deformity (ASD) surgery is complex and associated with high morbidity and complication rates. There is growing evidence in the literature for the beneficial effects of an approach to surgery in which two attending physicians rather than a single attending physician perform surgery for and oversee the surgical care of a single patient in a dual-attending care model. The authors developed a dual-attending care collaboration in August 2017 in which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 30 publications
(129 reference statements)
0
15
0
1
Order By: Relevance
“…They examined an ASD patient who underwent deformity correction surgery with a posterior-only approach in their case series. Several studies have reported the correction of ASD using LLIF, a frequent indication for LLIF [ 27 , 28 , 29 ]. Anterior release using LLIF techniques can correct misalignment in the coronal and sagittal planes and may even restore the disc height [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…They examined an ASD patient who underwent deformity correction surgery with a posterior-only approach in their case series. Several studies have reported the correction of ASD using LLIF, a frequent indication for LLIF [ 27 , 28 , 29 ]. Anterior release using LLIF techniques can correct misalignment in the coronal and sagittal planes and may even restore the disc height [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…This meta-analysis found surgical outcomes are likely unrelated to a surgeon’s subspecialty. However, improvement in outcomes is most likely in high surgical volume practices with neurosurgeons and orthopedic surgeon collaboration 39–42. As neurosurgeons and orthopedic spine surgeons have historically had different training backgrounds, spine patients likely stand to benefit from the unique skillsets and viewpoints that each subspecialty provides.…”
Section: Discussionmentioning
confidence: 99%
“…A joint or-tho-neuro program for challenging spine conditions is beneficial to both patients and care providers. 43…”
Section: The Futurementioning
confidence: 99%
“…The development is paralleled by the formation of interdisciplinary spine units in the larger Swiss public and university hospitals, e.g., in Basel, Lausanne, Zurich, and St.Gallen, which are composed of both neuro- and orthopedic surgeons. A joint ortho-neuro program for challenging spine conditions is beneficial to both patients and care providers [ 43 ].…”
Section: The Futurementioning
confidence: 99%